2016
DOI: 10.1515/icom-2016-0001
|View full text |Cite
|
Sign up to set email alerts
|

The Uncanny Valley and the Importance of Eye Contact

Abstract: Drift-current-pulses in semiconductors with vanishing dark conductivity measured according to the method of Kepler and LeBlanc deviate from the expected rectangular pulse shape even under ideal experimental conditions. In this work it will be shown that among other processes the diffusion of current carriers is responsible for the deviation. Under appropriate experimental conditions one is able to measure diffusion-constants in anthracene by a method to be described. Within experimental error the diffusion-con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…This could well be due to the interesting features of the avatar design, which might have been aesthetically appealing to the students. This finding is also in line with Schwind and J€ ager (2016), who stated that Asian-shaped eyes-with straight eyebrows and slightly increased size in relation to the average face-are considered more likeable and attractive than down-turned eyebrows or droopy eyes. On the other hand, the remaining avatar designs' mean value reflected a neutral, not negative, state in the arousal scale.…”
Section: Research Questionsupporting
confidence: 89%
See 1 more Smart Citation
“…This could well be due to the interesting features of the avatar design, which might have been aesthetically appealing to the students. This finding is also in line with Schwind and J€ ager (2016), who stated that Asian-shaped eyes-with straight eyebrows and slightly increased size in relation to the average face-are considered more likeable and attractive than down-turned eyebrows or droopy eyes. On the other hand, the remaining avatar designs' mean value reflected a neutral, not negative, state in the arousal scale.…”
Section: Research Questionsupporting
confidence: 89%
“…A participant's eye contact may determine the perception of artificial characters, and its role in decision-making regarding artificial faces, such as avatars. This was affirmed by Schwind and J€ ager (2016), whose study indicated that, whether with ordinary human characters or CGI characters, most attention was paid to the eyes (Figure 3). Surprisingly, another study by Schwind et al (2015) indicated that Asian-shaped eyes, bright and strong eyebrows, and slightly increased size in relation to the average face, were found to be more likeable and attractive, as ranked by the respondents.…”
Section: Eye Size and Uncanny Valley Phenomenonmentioning
confidence: 94%
“…Additionally, as the human-likeness and affinity ratings were both dependent and subjective variables in this study, we decided to measure human's fixation duration at the robot as an implicit measure to support and affirm the effect of the Uncanny Valley and the influence of robot's nonverbal behaviour. According to the previous studies, the correlations between likability and duration of eye fixations have been reported [40][41][42][43]. These previous studies asserted that the human's gaze or duration of eye fixations on the robot can be used as a measurement to evaluate the robot's perceived human-likeness and affinity toward the robot.…”
Section: Experimental Designmentioning
confidence: 99%
“…This may require greater authenticity from video games characters. Schwind & Jäger (2016) remarked also that human-CGI figures interaction could be improved by more credible eyes and eye-related areas. For example, in real life, it is natural to indicate our desired objects by focusing our eyesight on them.…”
Section: Still Uncannymentioning
confidence: 99%